Arabic Language Neologism on the Field of Technology in al-Akhbar Newspaper - Balkis Aminallah Nurul Mivtakh (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2019)
This study aimed to investigate Arab neologism in the field of technology in the al-Akhbar newspaper. Al-Akhbar newspaper is considered representative if it is used as a material object in research relating to the neology of the word technology. The perspective used in this study was morphological studies. The neologism theory is divided into five types and fifteen rules, including 1) phonetic neologism, which consists of: a) ibdal; b) al-qalbu al-makani; c) al-tamasul; d) al-tabayun; e) al-idqham. 2) morphological neology, which consists of: a) al-isytiqaq; b) al-naht; c) al-tarkib; d) al-mu‘jamah. 3) neologically semantic, which consists of: a) majaz; b) literal speech. 4) neological spontaneity, which consists of: a) al-irtijal haqiqi; b) al-irtijal al-itba‘. 5) borrowing neology, which consists of: a) dakhil; b) mu‘arrab. The results obtained from this study are that the al-Akhbar newspaper uses many patterns: 1) morphological neology, namely isytiqaq, at-tarkib. 2) semantic neology, namely majaz, literally tarjamah. 3) loan neology, namely ad-dakhil and mu’arrab.